Comparison of Intima-Media-Thichness, Brachialic Artery VF and VF Draining Vein CKD with Diabetes and Non-Diabetes Performed AVF-Brachiosephiccia at RSCM - Herwen, Herwen; Patrianef, Patrianef; Vidiawati, Dhanasari (Jurnal Locus Penelitian dan Pengabdian, 2025)
Brachiocephalic arteriovenous fistula (AVF) is the recommended vascular access for long-term hemodialysis. However, AVF failure rates remain high, particularly among patients with diabetes mellitus (DM). Diabetes contributes to vascular structural changes, such as increased intima-media thickness (IMT) and reduced volume flow (VF), which may affect AVF maturation success. To compare changes in IMT, brachial artery volume flow, and draining vein volume flow in chronic kidney disease (CKD) patients with and without DM who underwent brachiocephalic AVF creation. This was a retrospective cohort study conducted at Cipto Mangunkusumo National General Hospital between April and June 2025. A total of 42 CKD patients were enrolled and divided into two groups: 21 with DM and 21 without DM. IMT and volume flow were measured using Doppler ultrasound at weeks 0, 2, and 6 after AVF creation. Data were analyzed using the Mann-Whitney test and independent T-test, depending on data distribution. Forty two participants met the inclusion criteria. No significant differences were found between the DM and non-DM groups regarding changes in brachial artery IMT (p = 0.918), brachial artery volume flow (p = 0.538), or draining vein volume flow (p = 0.642) at week 6. Although both groups showed a trend of increased VF from week 0 to week 6, the differences were not statistically significant. There were no significant differences in changes in IMT, brachial artery volume flow, or draining vein volume flow between CKD patients with and without DM following brachiocephalic AVF creation.